BISERICA PENTICOSTALĂ DIN ROMÂNIA ȘI LIBERTATEA RELIGIOASĂ ÎN EPOCA POST-COMUNISTĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Pentecostal Church in Romania and Religious Freedom in the Post-Communist EraThe aim of the present paper is to provide a brief presentation of the evolution of religious freedom in Romania since the 1989 Revolution from the perspective of a Pentecostal believer. To better understand what this event meant for this denomination, first the situation of the Pentecostal movement in the interwar and communist times will be presented, and then survey the changes brought by the fall of the communist regime and how religious freedom evolved in the past three decades.